Evidence-based leadership, innovation, and entrepreneurship in nursing and healthcare : a practical guide to success - Melnyk, Bernadette Mazurek; Raderstorf, Tim (Springer Publishing Company, 2021)
"Evidence from numerous studies support that leadership and innovation are critical factors for organizational success and improved outcomes. Further, no change takes place and sustains without strong leadership. Although the United States spends more money on healthcare than any western world country, our health outcomes are poor. For example, the U.S. is the worst western world country for a women to give birth. Sick care continues to be the predominant paradigm and needs to be shifted to well care since 80 percent of chronic conditions can be prevented with healthy lifestyle behaviors. We also are living during a time when over 50 percent of clinicians are suffering from burnout, which is affecting the quality and safety of care. Solutions, including strong leaders and innovators, are urgently needed"-- Provided by publisher